Mechanical investigation of rock-proppant interaction with focus on geothermal applications. Issue 1 (August 2021) - Witte, L; Pollmann, N; Backers, T
Abstract: Since decades proppants have been used to enhance hydraulic pathways for the exploitation of hydrocarbon reservoirs. These technologies may also be adapted for geothermal applications, but geothermal reservoirs rocks strongly differ from those typically targeted by hydrocarbon industries. Therefore, the mechanical interaction between conventional proppants and geothermal reservoir rocks and their effect on hydraulic properties need to be investigated in more detail to maximize the success of such method adaption. In principle, two mechanical requirements must be fulfilled: (1) proppants must withstand the stresses that are present in a reservoir, and (2) proppants must not penetrate the rock formation of the reservoir, because this would reduce the fracture conductivity. Fine mobilized rock- or proppant particles can also clog the fracture. For the mechanical suitability of proppants, uniaxial compressive strength tests and long-term creep tests were carried out in the laboratory. The test setup consists of a proppant monolayer placed between two cylindrical rock samples that were axially loaded. We determined Young's moduli and creep rates for sample stacks with various proppants under different stress conditions. The laboratory tests are part of the ZoKrateS Project, which aims at showing the feasibility of enhancing fractured carbonate rock mass by proppant placement for geothermal applications.